RISK MANAGEMENT OF COMPLICATIONS OF SURGICAL TREATMENT OF COLORECTAL CANCER BY CORRECTION OF THE HEMOSTASIS SYSTEM - Appelhans, O.L.; Duzenko, O.O.; Tarabrin, O.O.; Zaporozhchenko, M.B. (World of Medicine and Biology, 2021)
In 72 patients with verified colorectal cancer (T2-4N0-2M0-1), who were planned and performed surgical intervention in order to prevent complications, including thrombohemorrhagic complications, comorbid burden was studied according to the Charlson comorbidity index questionnaire and the results of study of hemostatic potential (low-frequency piezothromboelastography) after functional test with double local ischemia of the upper limb. The predicted relative risk of thrombohemorrhagic complications was high (relative risk THC=3.2; p=0.017). In the patients with III–IV stages of the disease, the results of low-frequency piezothromboelastography corresponded to the decompensated or depleted type of reaction of the hemostasis system (r=0.59; p=0.036). Depending on the disorders identified in the patients, the following were used: antiplatelet agents, direct anticoagulants, bioflavinoids, cofactors of the components of the coagulation system, antifibrinolytic drugs. The use of the developed prophylaxis regimens made it possible to reduce the incidence of postoperative complications, the total share of which was 8.4 %, including: pulmonary embolism occurred in 1.4 % of cases and hemorrhagic complications – in 2.8 %.
Keywords: prognosis; risk; complications; colorectal cancer; surgical treatment; low-frequency piezothromboelastography